The realationship between the covid-19 pandemic and the stock market indexes of sports clubs: a time series analysis - PEKEL, AYDIN (My University, 2023)
The present study examines how severely the stock market indexes of the sports clubs in Turkey and Europe were affected and by which factors between 16.03.2020 and 14.12.2020 in addition to the coronavirus cases and deaths in the pandemic process using empirical methods. Additionally, the number of cases and death rates during the pandemic are analyzed graphically by country. In the empirical application section, the Toda-Yamamoto (1995) test was applied. Before moving on to the causality analysis, the extended Dickey-Fuller test was used to determine whether the series possessed a unit root. In the present study, which covers the period between 16.03.2020 and 14.12.2020, the case and death data of countries were used to reveal the relationship between the stock market indexes of the sports clubs in Turkey and Europe and the number of COVID-19 cases and deaths. As a result of the study, no significant value was determined between the stock market index series of sports clubs and the number of COVID-19 cases and deaths. No short-term relationship was found between the stock market indexes of sports clubs and the number of cases and deaths. Keywords: COVID-19, Sports Clubs, Time Series Analysis.
Keywords: Spor Yönetim Bilimleri; Sport Management Sciences; Sosyal Bilimler (SOC); Sosyal Bilimler Genel; EĞİTİM, BİLİMSEL DİSİPLİNLER; Social Sciences (SOC); SOCIAL SCIENCES, GENERAL; EDUCATION, SCIENTIFIC DISCIPLINES